Análise de uma disciplina da Pedagogia fundamentada na abordagem CCS: políticas educacionais, formação inicial e TDIC - COIMBRA, Ana Cristina Cardoso (2020)
This dissertation is linked to the research line “Public Policies in Education, Formative Processes and Diversity” at the University of Western São Paulo Graduate Program of Education (UNOESTE / PPGE). This research is justified by the importance of pointing out ways for teacher training according to the Brazilian educational policies, proposing a different and new strategy for training students through the CCS approach, making learning meaningful and using Digital Information and Communication Technologies (DICT) as tools during the teaching and learning processes. A qualitative action research was conducted with the general objective of analyzing the processes of planning and developing the Libras (Brazilian Sign Language) course for Inclusive Education in a Pedagogy program according to the principles of the Constructionist, Contextualized and Meaningful (CCS from the acronym in Portuguese) approach. First, a bibliographic review of the scientific production published from 2017 to 2019 was conducted, along with the analyses of the educational policies in the last 30 years and the initial teacher training processes. The research was developed during the second semester of 2019, with a total of 15 4-hour-class sessions. In order to participate in all phases of the teaching and learning processes, the researcher worked together with the professor of the course and his students. The participants were 1 professor and 60 students of the Libras course in the Pedagogy program at a public state university located in the interior of São Paulo State, Brazil. Data were collect and organized through questionnaires, field diaries, and activities developed by students, and, subsequently, interpreted in the light of data triangulation based on the discussion of educational policies and the literature that discusses teacher training. As a result, it was possible to ascertain that, despite the initial resistance related to the change in educational practice, the students managed to elaborate a project for an inclusive school, reflecting on how to include Students Target Audience of Special Education (EPAEE from the acronym in Portuguese) in the school environment, using the DICT as tools for the construction of knowledge and as a resource of Assistive Technology (AT) for inclusion in the classroom. As a final analysis, the findings demonstrated that the educational policy used to proactively guide Higher Education Institutions (HEIs) assists in the execution of inclusive projects. In addition, the adoption of approaches such as CCS in curricula, combined with project work, favors the development of autonomy, the reflection on educational practice and the use of DICT as tools for building knowledge and as resources to support AT for EPAEE.